Sluggish dorsally-driven inhibition of return during orthographic processing in adults with dyslexia. - Franceschini, S.; Mascheretti, S.; Bertoni, S.; Trezzi, V.; Andreola, C.; Gori, S.; Facoetti, A. (Brain & Language, 2018)
Dyslexia (D) is a neurodevelopmental reading disorder characterized by phonological and orthographic deficits. Before phonological decoding, reading requires a specialized orthographic system for parallel letter processing that assigns letter identities to different spatial locations. The magnocellular-dorsal (MD) stream rapidly process the spatial location of visual stimuli controlling visuo-spatial attention. To investigate the visuo-spatial attention efficiency during orthographic processing, inhibition of return (IOR) was measured in adults with and without D in a lexical decision task. IOR is the delay in responding to stimuli displayed in a cued location after a long cue-target interval. Only adults with D did not showed IOR effect during letter-string recognition, despite the typical left-hemisphere specialization for word identification. A specific deficit in coherent-dot-motion perception confirmed an MD-stream disorder in adults with D. Our results suggest that adults with D might develop an efficient visual word form area, but a dorsal-attentional dysfunction impairs their reading fluency.